MOUTHRINSES AND POTENTIAL FOR HARM TO ORAL HEALTH: OBAT KUMUR DAN POTENSI UNTUK MENIMBULKAN KELAINAN TERHADAP KESEHATAN RONGGA MULUT - Natalina (Dentika: Dental Journal, 2010)
Oral care product produced primarily to benefit oral and dental health. Throughits role in the prevention and treatment ofgingival and periodontal disease, there is the potential for benefits of oral hygiene p roduct in the prevention of systemicdisease and conditions. All agents, drug and devices designed to maintain and improve human well being, there is thepossibility of harmful side effects occurring as a result of the use of oral hygiene products. This re view is to debate thepotential for oral hygiene products, when used as recommended, to cause oral and dental harm to the user. Mouth rinseswould appear to ha ve potential risks/ side effects originally from three sources such as the physico chemical proper ties,the active in the product and other ingredients. Any physical trauma to the gingival, particularly if inflamed, can produce abacteremia. The importance of mouth rinses to the periodontal patient must be far outweigh the potential harm in use toden t al hard tissues or the gingiva In conclusion, the use of mouth rinses properly based on regulat ed pack and followeddentist in gestoon would not cause side effects of oral cavity realth.